Changes in in vitro rumen fermentation parameters of crossbred cattle (Bos taurus) and buffalo (Bubalus bubalis) in response to diet at different time intervals - DIXIT, SONAM; KUMAR, SACHIN; TYAGI, A K (The Indian Journal of Animal Sciences, 2022)
Assessment of the diet adaptation period is critical for feeding experiments in ruminants to have significant changes in the concerned parameters. An in vitro trial was conducted to investigate the impact of the sampling at different time periods (day 0, 11, 21, and 60) to determine the adaptation period of feed treatment over the ruminal fermentation parameters in crossbred Karan-Fries cattle (Bos taurus) and Murrah (Bubalus bubalis) heifers. Two types of total mixed rations (TMRs), viz. high forage diet (HFD) having roughage and concentrate ratio (R:C) as 70:30 and high concentrate diet (HCD) having R:C as 40:60 were formulated, and fed to cattle and heifers. Rumen liquors were collected from all the animals on 0, 11, 21, and 60 days. HFD and HCD diets were incubated with strained rumen liquor collected from cattle and buffalo adopting Menke’s in vitro gas procedure. The results showed that most of the in vitro rumen fermentation parameters, viz. total volatile fatty acids (TVFAs) (mM/ml), acetate (%), propionate (%), butyrate (%), acetate propionate ratio (A:P), partitioning factor (PF) and microbial biomass production (MBP) (mg), in vitro dry matter digestibility (IVDMD) (%) and in vitro organic matter digestibility (IVOMD) (%) were significantly different at day 0 and 11 compared to day 21. Afterward, up to day 60, there were no effects reported except increased IVDMD and IVOMD for buffalo compared to day 21. As a result of our findings, it can be concluded that there are significant differences in rumen fermentation parameters at 11 and 21 days and that the time period for cattle and buffalo should not be reduced to 11 days from 21 days in order to achieve proper feed adaptation and stabilize the rumen fermentation process. Further research is needed to investigate the impacts of the adaption period at various time intervals.